Peran Filsafat Ilmu Tentang Konsep Teori Kebenaran Ilmiah - Nur, Isnawia Djou; P. Ola, Sumarni; Pahmi, Samsul (Jurnal BELAINDIKA (Pembelajaran dan Inovasi Pendidikan), 2024)
Philosophy of science plays a vital role in understanding and developing theories of truth in science. Theories of scientific truth encompass a range of concepts that influence how we view scientific knowledge and the methods by which it is established. Philosophy of science plays a fundamental role in the development of science by exploring basic concepts, including theories of scientific truth. Scientific truth is a principle that seeks to ensure that knowledge obtained through the scientific process is valid, testable, and universally accepted. Philosophy of science discusses various theories of truth, such as correspondence theory, coherence theory, pragmatic theory, and consensus theory, each of which offers a different approach to determining the validity of scientific knowledge. This paper explores how these concepts of theories of truth are applied in scientific research, including the role of verification and falsification in the scientific method, and how philosophy of science contributes to shaping standards of truth accepted in the scientific community. This study aims to understand how philosophy of science, through various theories of truth, contributes to improving the accuracy, validity, and objectivity of scientific research results. Thus, this study not only highlights the role of philosophy of science in providing a philosophical foundation for scientific truth, but also how philosophy of science encourages critical, reflective, and ever-evolving scientific practices.